From paradise to the promised land : an introduction to the Pentateuch - Alexander, T. Desmond (Grand Rapid, MI : Baker Academic, a division of Baker Publishing Group, 2022)
This text has been a popular introduction to the Pentateuch for over fifteen years, offering a unique alternative to the critical approaches that focus on the composition of these books rather than the actual content. With this new edition, T. Desmond Alexander keeps the book fresh and relevant for contemporary students by updating the references and adding material that reflects recent pentateuchal research as well as the author's maturing judgments. The result is a revision that will prove valuable for many years to come. - Publisher.
Pentateuchal criticism. Introduction to Pentateuchal criticism -- The rise of the documentary hypothesis -- Going behind the documents -- The documentary hypothesis under threat -- The Sinai narrative : a test case -- The future of studies -- The main themes of the Pentateuch. An overview of the Pentateuch -- God's temple-city -- The royal lineage in Genesis -- The blessing of the nations -- Paradise lost -- By faith Abraham -- Who is the Lord? -- The Passover -- The covenant at Sinai -- The tabernacle -- Be holy -- The sacrificial system -- The clean and the unclean foods -- Toward the promised land -- Murmurings -- Love and loyalty -- Why Israel? -- The Pentateuch and the biblical metanarrative.
Includes bibliographical references (p. 315- 335) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc